PI-fuzzy logic control for 3 phase BLDC motor for electric vehicle application - Ibrahim, Babul Salam K.K.; Mohd Azubir, Nor Aziah; Ishak, Norlela; Hassan, Mohd Khair; Toha, Siti Fauziah; Zainul Abidin, Mohd Azman; Ismail, Hashimah; Zamzuri, Hairi (2012)
Brushless DC motor has been widely used in electric vehicle because of its high performance and simplicity. However this motor is a multi-variable, non-linear system and easily can be influenced by the parameter variations and disturbances. The conventional controllers are unable to handle this problem. To overcome this problem a nonlinear PI-fuzzy logic controller is used to control the speed of electric vehicle traction motor. The development of this control strategy is presented in this paper. The proposed controller has simple structure and also due to its modest fuzzy rule in rulebase is relatively easy for implementation. The control is performed by Matlab/Simulink software. The simulation test results have been satisfactory in both steady and transient states. This controller has high accuracy, suitable performance, high robustness and high tracking efficiency.